2008
DOI: 10.1111/j.1442-2042.2008.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel β3‐adrenoceptor agonist, AJ‐9677, on relaxation of the detrusor muscle: An in vitro study

Abstract: Objectives:To examine the relaxant effects of AJ-9677, a novel b3-adrenoceptor agonist, on the isolated rat, monkey and human detrusor muscle. Methods: The isolated detrusor strips of rats, monkeys and humans were mounted in organ baths containing Krebs solution. By the cumulative addition of b-adrenoceptor agonists (isoproterenol, AJ-9677, CL 316,243 and salbutamol in rats; isoproterenol, AJ-9677 and CL 316,243 in monkeys and humans), concentration-relaxation curves were obtained. The maximal relaxation respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Thus, isoproterenol responses were inhibited by SR58894 but only poorly by CGP 20712A or ICI 118551 (Igawa et al 1999) or inhibited by SR59230A but only poorly by atenolol or butoxamine . Antagonism of isoproterenol responses by SR59230A has also been reported by others in isolated human bladder strips (Otsuka et al 2008a;Frazier et al 2011) and was reproduced in our present study. On the other hand, SR59230A yielded only limited inhibition of the human detrusor relaxation response to solabegron (Biers et al 2006) or nebivolol (Frazier et al 2011).…”
Section: Detrusor Relaxation Findingssupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, isoproterenol responses were inhibited by SR58894 but only poorly by CGP 20712A or ICI 118551 (Igawa et al 1999) or inhibited by SR59230A but only poorly by atenolol or butoxamine . Antagonism of isoproterenol responses by SR59230A has also been reported by others in isolated human bladder strips (Otsuka et al 2008a;Frazier et al 2011) and was reproduced in our present study. On the other hand, SR59230A yielded only limited inhibition of the human detrusor relaxation response to solabegron (Biers et al 2006) or nebivolol (Frazier et al 2011).…”
Section: Detrusor Relaxation Findingssupporting
confidence: 85%
“…Based on the potency and efficacy of the reference agonists isoproterenol, noradrenaline, and adrenaline; the β1-agonist dobutamine; the β2-agonists clenbuterol, procaterol, salbutamol, and terbutaline; and the β3-agonists 138- 17, 4.79±0.38, and 5.59±0.72, respectively 355, AJ-9677, BRL 37344, CL-316243, GS 332, L 755,507, mirabegron, solabegron, and ZD 7114, it has generally been claimed that human detrusor smooth muscle relaxation is a β3-AR-mediated response (Badawi et al 2005(Badawi et al , 2007Biers et al 2006;Igawa et al 1998Igawa et al , 1999Igawa et al , 2001Li et al 2003;Morita et al 2000;Nomiya and Yamaguchi 2003;Otsuka et al 2008a;Takasu et al 2007;Takeda et al 1999;Yamanishi et al 2006). The potency and efficacy of isoproterenol, clenbuterol, and BRL 37344 in the present study is in line with those previous reports and validates our preparation.…”
Section: Detrusor Relaxation Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…18 Although further studies are needed to uncover which environmental exposures constitutes the link between asthma and overactive bladder it is noteworthy that β3-agonists, initially intended for the treatment of asthma, are prescribed for the treatment of overactive bladder. 19, 20 …”
Section: Discussionmentioning
confidence: 99%
“…Novel Therapies β3-Adrenoceptor stimulation causes bladder relaxation and is therefore being evaluated as a possible treatment of OAB. The β3 agonist AJ-9677 promotes bladder relaxation in rat, monkey and human detrusor tissue in vitro [68]. An evaluation in rats showed that intravesical administration of two different β3 agonists promoted bladder relaxation [69].…”
Section: Current Overactive Bladder Treatmentsmentioning
confidence: 98%